When Words Become a Trap - D. Klus-Stanska (Moscow Polytechnic University, 2019)
The paper is an attempt to analyze the language of the Polish core curriculum for primary schools and the language of teaching methodology, created by the core curriculum, as a source of stereotype thinking about school and the (im)possibility of changing the model of education. In this perspective, the language of methodological documents appears as a significant barrier to changes in the educational system, perpetuating traditional teaching, and leading to the blocking of the development of students.